2019
DOI: 10.1111/1462-2920.14728
|View full text |Cite
|
Sign up to set email alerts
|

Communal metabolism by Methylococcaceae and Methylophilaceae is driving rapid aerobic methane oxidation in sediments of a shallow seep near Elba, Italy

Abstract: Summary The release of abiotic methane from marine seeps into the atmosphere is a major source of this potent greenhouse gas. Methanotrophic microorganisms in methane seeps use methane as carbon and energy source, thus significantly mitigating global methane emissions. Here, we investigated microbial methane oxidation at the sediment–water interface of a shallow marine methane seep. Metagenomics and metaproteomics, combined with 13C‐methane stable isotope probing, demonstrated that various members of the gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…3a, b). The shift of the MOB assemblage was accompanied by a drop in temperature and rise in oxygen, which are probable drivers of MOB succession in addition to methane availability (Hernandez et al, 2015;Oshkin et al, 2015;Trotsenko and Khmelenina, 2005). This did, however, not lead to much change in the methane affinity ( Fig.…”
Section: Dynamics Of the Mob Assemblage And Variants Of Pmmomentioning
confidence: 96%
See 1 more Smart Citation
“…3a, b). The shift of the MOB assemblage was accompanied by a drop in temperature and rise in oxygen, which are probable drivers of MOB succession in addition to methane availability (Hernandez et al, 2015;Oshkin et al, 2015;Trotsenko and Khmelenina, 2005). This did, however, not lead to much change in the methane affinity ( Fig.…”
Section: Dynamics Of the Mob Assemblage And Variants Of Pmmomentioning
confidence: 96%
“…The fact that both the affinity and maximum rate are higher would intrinsically suggests that the assemblage in the epilimnion has a competitive advantage over the assemblage in the hypolimnion. This implies that there were likely additional mechanisms or traits, like adaptation to oxygen concentration or temperature (Hernandez et al, 2015;Trotsenko and Khmelenina, 2005), that prevented the epilimnetic MOB assemblage from invading the assemblage in the hypolimnion. We already have strong indications from our previous work that these factors are indeed important (Mayr et al, 2020a, b).…”
Section: Succession Of Kinetically Different Microbial Communitiesmentioning
confidence: 99%
“…Recovering representative sequences such as OTUs or ASVs allows for further analysis like constructing phylogenetic trees or performing targeted analyses, such as searching for the same sequence or related sequences in other data sets, that is not possible when using direct read classification. However, direct taxonomic classification can be straight forward with functional gene sequences that do not have elaborate reference databases like the 16S rRNA gene (DeSantis et al, 2006;Quast et al, 2013), e.g., for methane monooxygenase genes (pmoA, mmoX) or methanol dehydrogenase genes (xoxF4, xoxF5, mxaF) (Taubert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of methanotrophs to limit CH 4 emission has previously been shown, e.g., Bornemann et al (2016) used pMMO primers (subunit A, pmoA) and clone-libraries to identify methanotrophs (taxonomic order Methylococcales) in the pelagic area of Lake Constance, and found that these bacteria contributed substantially to CH 4 removal in the bottom water directly above the sediment surface. Bacterial members belonging to the order Methylococcales are ubiquitous (Smith et al, 2018), and metagenome plus metatranscriptome analysis have shown that they dominate aerobic CH 4 oxidation in wetland soil (Smith et al, 2018), and are important in removing CH 4 escaping from benthic CH 4 seeps (Taubert et al, 2019). Methanotrophs are therefore essential key players in regulating CH 4 emission to the atmosphere from aquatic environments.…”
Section: Introductionmentioning
confidence: 99%